Externalities, fixed costs and information. - Keppler, Jan Horst (Kyklos, 1998)
The writer contends that Pigou's and Coase's well-known theoretical solutions to the problem of externalities—bargaining under low transaction costs, taxation according to measured preferences—have merely restated “the problem of social cost,” rather than tackling it. He reiterates the fact that externalities exist where preferences are difficult to measure and transaction costs are high. Using Arrow's hypothesis that the existence of externalities is equivalent to the non-existence of markets, he demonstrates that externalities are characterized by high transaction costs and informational complexity. He then presents institution-based approaches as an appropriate response capable of addressing the complexity and the dynamic nature of externalities.